The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1017/s0021932016000018
|View full text |Cite
|
Sign up to set email alerts
|

Rumours, Riots and the Rejection of Mass Drug Administration for the Treatment of Schistosomiasis in Morogoro, Tanzania

Abstract: SummaryIn 2008 in Morogoro region, Tanzania, mass drug administration (MDA) to school-aged children to treat two neglected tropical diseases (NTDs) – urinary schistosomiasis and soil-transmitted helminths – was suspended by the Ministry of Health and Social Welfare after riots broke out in schools where drugs were being administered. This article discusses why this biomedical intervention was so vehemently rejected, including an eyewitness account. As the protest spread to the village where I was conducting fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…Additionally, rumours and refusals were evident in the community, partly owing to misinformation. Rumours may also have historical or political origins or result from cultural beliefs (Parker et al, 2008Hastings, 2016. Rumours of health interventions causing sterility or containing contraceptives have been documented since the 1920s in Africa, including vaccinations, malaria treatment and vitamin supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, rumours and refusals were evident in the community, partly owing to misinformation. Rumours may also have historical or political origins or result from cultural beliefs (Parker et al, 2008Hastings, 2016. Rumours of health interventions causing sterility or containing contraceptives have been documented since the 1920s in Africa, including vaccinations, malaria treatment and vitamin supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The Maasai have a very strong sense of cultural identity, which is expressed in beliefs, norms and traditions. There is a tendency for public health interventions to expect communities to place high importance on their programme with poor consideration of how interventions fit into the communities' priorities and the complexity of livelihoods (Parker et al, 2008;Bardosh, 2014b;Hastings, 2016;Martineau et al, 2017). Communities are a social network influencing norms and behaviours.…”
Section: Domain 2: Socio-cultural Factors and Community Agencymentioning
confidence: 99%
“…In other words, deworming alone was largely ineffective. Since 2005, research undertaken by the authors and their students has found comparable problems in other parts of East Africa (Aldis, 2008;Wingate-Saul & Shira, 2008;Parker et al, 2008Parker et al, , 2012Parker & Allen, 2011, 2013aOzunga, 2014;Pearson, 2016;Hastings, 2016). Field sites were located in north-western Uganda (Nebbi, Buliisa, Adjumani and Moyo Districts), south-eastern Uganda (Busia District -just across the border from where Miguel and Kremer studied deworming in Kenya), Tanzania's Ukerewe Island in Lake Victoria, Tanga Region in northern coastal Tanzania, and Morogoro Region, which lies to the west of Dar es Salaam (see Fig.…”
Section: Doing Deworming In East Africamentioning
confidence: 90%
“…Such experiences and stories led to widespread anxiety and fear, and fostered rumours about the real purpose of the treatments. They also prompted a different kind of resistance in the form of a refusal to distribute or take the tablets, and occasionally confrontations with angry parents (Parker & Allen, 2011;Hastings, 2016).…”
Section: Deeper Deworming Doubtsmentioning
confidence: 99%
“…Sub-Saharan African countries with about 90% of the world's total cases are the most affected regions [ 3 ]. In Nigeria, 20 million people need to be treated annually, thus, it is the most affected country in the world [ 4 ]. School-based deworming with Praziquantel (PZQ) is the main intervention for schistosomiasis in Nigeria.…”
Section: Introductionmentioning
confidence: 99%